SURGICAL OUTCOMES OF STRABISMUS CORRECTION IN LARGE ANGLE EXOTROPIA - Sadida, Rahmah; Ekowati, Liana; Saubig, Arnila Novitasari (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction and Objective: Surgery is one of the treatment options for strabismus. The success rates of surgical interventions, as reported in a number of different studies, vary widely. There is no database of surgical outcome in large angle exotropia patient undergoing surgery in Semarang, Central Java. This study aims to evaluate the surgical outcome of strabismus correction in large angle exotropia in Dr. Kariadi General Hospital. Methods: A retrospective study held from the medical record of patients with diagnosis large angle (>50?) exotropia undergoing strabismus correction surgery from January 2020-December 2022 in Dr. Kariadi General Hospital, Semarang. The clinical characteristics: sex, age, angle of exodeviation, amblyopia condition, sensory deprivation, and postoperative alignment were obtained. Surgical outcome measured with follow up of angle deviation in one month dan three months follow up after surgery. Result: Totally 59 large angle exotropia patients were obtained with 31 (53%) were woman and 28 (47%) were man, range aged 1 year to 53 years old had preoperative angle of exodeviation 51->85 ?, 6 (10%) had amblyopia, 11(18.6%) had sensory deprivation. By the 3 months post-operative visit, 100% of all patients reported orthophoria. Conclusion: This study found the outcome of strabismus correction for large angle exotropia is satisfactory. Two- or three-muscle surgery provides an effective means for treatment of large angle exotropia. Keywords: large angle exotropia, exodeviation, strabismus